Ludic Images (Büchner-Verlag, 2026)
»Ludic Images« explores the dynamic interplay of moving images, games, and interactive media. In the wake of the digital turn, playful and game-related aesthetics have emerged as central forces in shaping contemporary image cultures—from cinematic cut scenes and augmented reality games to virtual reality environments and mobile interfaces. This volume investigates the technological, aesthetic, and narrative dimensions of ludic images, connecting game design, digital scenography, and interactive media practices with approaches from media theory, philosophy, art and design, perceptual studies, semiotics, computer graphics, and image science. By examining the sensory, cultural, and cognitive conditions of playful images, »Ludic Images« contributes to a deeper understanding of how games, interactivity, and digital imagery transform our modes of perception, narration, and participation in the postmodern image era.